THE CHILDFREE PHENOMENON AMONG URBAN MUSLIMS: A MULTIDISCIPLINARY EXAMINATION OF SCIENCE AND MORALITY - Sukron Ma'mun; Sheikh Adnan Ahmad Usmani; Ibnu Akbar Maliki (Akademika : Jurnal Pemikiran Islam, 2023)
The concept of childfree represents a multifaceted issue, influenced by a diverse array of factors, including economic, cultural, social, and philosophical considerations. A comprehensive understanding of the childfree phenomenon necessitates an approach that extends beyond strict reliance on religious interpretation, incorporating other scientific disciplines. Therefore, the integration of morals and science through a multidisciplinary framework becomes imperative. In this context, the mubadalah approach, aligned with the integration-interconnection paradigm, emerges as a suitable methodology for unravelling the complexities of childfree within society. This article endeavours to analyse childfree from the perspective of mubadalah, prioritizing the dialogue between science and morality within the context of marriage. The research methodology employed is descriptive qualitative, employing a literature study approach. The findings reveal that employing the semipermeable mubadalah method to analyse the position of childfree in society has led to the emergence of three new perspectives: the just perspective, the humanist perspective, and the perspective rooted in the value of tawhid. These three perspectives encompass the following notions: firstly, the presence of children assumes a central role in the marital union, requiring thoughtful consideration by both partners; secondly, childfree is not solely a matter of fitrah (innate human disposition), but also involves psychological and moral dimensions; and finally, childfree, from a medical standpoint, is permissible within the context of Islam. These perspectives, derived from medical disciplines, moral frameworks, and religious interpretations, contribute to a nuanced understanding of childfree.